A computational investigation of the properties of a reverse osmosis membrane - Hughes, Zak; Gale, Julian (The Royal Society of Chemistry, 2010)
Reverse osmosis (RO) is currently one of the most widely used methods of desalination in the world and rapidly increasing in usage. The membranes used in the RO process play a vital role in determining the effectiveness of the desalination process. In this work, fully atomistic molecular dynamics simulations of one of the most widely employed membranes, namely the FT30 polyamide material, have been carried out in order gain greater understanding of the structure of the system and its interaction with saline solution. The system studied consisted of a solvated membrane layer and a layer of bulk solution, thus allowing the membrane interface to be simulated. The behaviour of water and salt ions in both thebulk solution and membrane has been investigated. It was found that the diffusivities of water and the salt ions were reduced by an order of magnitude within the membrane. Furthermore, umbrella sampling methods have been used in order to determine the free energy surface associated with the salt ions passing through the membrane-solution interface. The present work demonstrates that there is a high degree of variability in the resistance to salt diffusion into the membrane associated with the structure of the water encountered as the ion permeates the membrane. Despite this variability in the free energy gradient, all cases ultimately exhibit a high resistance to ionic diffusion due to charge separation. However, migration of a sodium cation/chloride anion pair fails to substantially lower the barrier to salt diffusion, thus confirming the robust nature of the membrane selectivity for water.